2018
DOI: 10.1002/brb3.1014
|View full text |Cite
|
Sign up to set email alerts
|

Sodium metavanadate induced cognitive decline, behavioral impairments, oxidative stress and down regulation of myelin basic protein in mice hippocampus: Ameliorative roles of β‐spinasterol, and stigmasterol

Abstract: IntroductionExposures to toxic levels of vanadium and soluble vanadium compounds cause behavioral impairments and neurodegeneration via free radical production. Consequently, natural antioxidant sources have been explored for effective and cheap remedy following toxicity. Grewia carpinifolia has been shown to improve behavioral impairments in vanadium‐induced neurotoxicity, however, the active compounds implicated remains unknown. Therefore, this study was conducted to investigate ameliorative effects of bioac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…Although limited in number, there are studies evaluating the effects of phytosterols on vanadium-induced toxicity, as described below. The oral administration of stigmasterol and β-sitosterol significantly attenuated neurobehavioral impairments such as deficits in exploration, learning and 7 Oxidative Medicine and Cellular Longevity memory disabilities, and decreased motor coordination, which were induced by sodium metavanadate in mice [106,107]. Additionally, in these studies, the two sterols mentioned above exerted an inhibitory effect on hydrogen peroxide generation and lipid peroxidation and improved the activities of superoxide dismutase and catalase in brain tissue of vanadium-exposed mice.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Although limited in number, there are studies evaluating the effects of phytosterols on vanadium-induced toxicity, as described below. The oral administration of stigmasterol and β-sitosterol significantly attenuated neurobehavioral impairments such as deficits in exploration, learning and 7 Oxidative Medicine and Cellular Longevity memory disabilities, and decreased motor coordination, which were induced by sodium metavanadate in mice [106,107]. Additionally, in these studies, the two sterols mentioned above exerted an inhibitory effect on hydrogen peroxide generation and lipid peroxidation and improved the activities of superoxide dismutase and catalase in brain tissue of vanadium-exposed mice.…”
mentioning
confidence: 64%
“…Additionally, in these studies, the two sterols mentioned above exerted an inhibitory effect on hydrogen peroxide generation and lipid peroxidation and improved the activities of superoxide dismutase and catalase in brain tissue of vanadium-exposed mice. Therefore, the authors proposed that the neuroprotective effects of stigmasterol and β-sitosterol could be associated with reduced levels of oxidative stress [106,107]. The exact mechanism of the antioxidant activity of phytosterols is not well understood.…”
mentioning
confidence: 99%
“…More precisely, stigmasterol could reduce escape latency and prolong swimming time in Morris water maze. Also, stigmasterol could promote activities of antioxidant enzymes, and inhibit oxidative stress markers as well as lipid peroxidation in mice hippocampal homogenates [ 69 ]. A recent study showed that stigmasterol could protect mice from LPS-induced fever response.…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…13 In addition, vanadium has been shown to have effects on the nervous system, where it has been established to cross the blood-brain barrier, [14][15][16] bioaccumulate in brain tissue 16 and exert (acute and chronic) neuropathologies and behavioural deficits. [17][18][19][20][21][22][23][24] Much like the brain, the peripheral nervous system is characterised by highly peroxidizable fatty acids tissue, low levels of antioxidants and high aerobic metabolism. 25 These features put together, render this system highly susceptible to oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the vanadium‐induced pathologies reported on various organ systems include: the lungs, liver, spleen, and testes, haematological and biochemical alterations and the kidneys . In addition, vanadium has been shown to have effects on the nervous system, where it has been established to cross the blood‐brain barrier, bioaccumulate in brain tissue and exert (acute and chronic) neuropathologies and behavioural deficits …”
Section: Introductionmentioning
confidence: 99%